Antecedents of Trust in Artificial Intelligence: A Literature Review - Peter RITTGEN (Communications of International Proceedings, 2025)
The rise of Artificial Intelligence (AI) in information systems offers a host of new opportunities but also substantial challenges. In 2019 the EU commission released the “Ethical Guidelines for Trustworthy AI”. So far, these guidelines are only recommendations and not enforced by law. Six years after their release it is still unclear how these guidelines can be put into practice. Maturity with respect to the ethical use of AI is still limited in organizations so a deeper look into the status quo of research in this area seems imperative. We started by doing an exploratory literature study to find the most relevant antecedents determining trust in AI. We then proceeded by performing an in-depth literature review on how these antecedents, and thereby ultimately trust, can be achieved. Our results indicate that trust is an inherently complex issue that is still poorly understood.
Keywords: Ethics in Artificial Intelligence; trust; antecedents